Molecular delineation of the Agave Red Worm Comadia redtenbacheri (Lepidoptera: Cossidae) - Cárdenas-Aquino, María Del Rosario; Alarcón-Rodríguez, Norma Marina; Rivas-Medrano, Mario; González-Hernández, Héctor; Vargas-Hernández, Mateo; Sánchez-Arroyo, Hussein; Llanderal-Cázares, Celina (Zootaxa, 2018)
Comadia redtenbacheri (Hammerschmidt) (Agave Red Worm) is the only member of the family Cossidae that has been described as a phytophagous specialist of the plant genus Agave, which is mainly distributed in México. A new extraction protocol adapted from Stewart & Via (1993) has been implemented for sequencing the COI gene from samples collected in five states of the North Central (Querétaro and Zacatecas), South Central (Estado de México) and East Central (Hidalgo and Tlaxcala) regions of México with the purpose of contributing to delineation of the species. A Maximum Likelihood (ML) tree based on these COI sequences as well as COI sequences from other Cossinae species was developed to complement the existing morphological and taxonomic approaches to delineation of this species. As expected, our Comadia samples cluster together within a monophyletic clade that includes four C. redtenbacheri sequences previously reported. This group seems to be consistent with our reconstruction, which is supported by a bootstrap value of over 99%. The closely related branches associated with the latter group include organisms known to be the plant and tree borers of the Cossinae subfamily. The COI sequences from our samples were analyzed to determine the percentage of identity among the C. redtenbacheri in a first attempt to detect differences in the sequence that matches a particular region of México.